Fungi as a Sustainable Solution for Heavy Metal Removal in Wastewater Treatment: Jamur sebagai Solusi Berkelanjutan untuk Menghilangkan Logam Berat dalam Pengolahan Air Limbah - Roaa Hassan Al-Tayef; Raad Abdalrazaq Hamdi (Academia Open, 2024)
This study investigates the ability of non-living fungal biomass from Aspergillus terreus, Rhizopus oligosporus, and Rhizopus arrhizus to reduce heavy metal concentrations in wastewater. Using non-living fungal blocks, the experiment targeted the removal of lead (0.70 ppm), cadmium (0.110 ppm), and copper (0.80 ppm) from wastewater at the Al-Dur district sewage treatment station. Conducted under controlled conditions (25 degrees Celsius, pH 6.5-7.6) over a 24-hour period, the results demonstrated significant reductions in metal concentrations, with statistical significance at P<0.01. These findings suggest that non-living fungal biomass could be a cost-effective and environmentally friendly alternative for heavy metal remediation in wastewater treatment. Highlights: Fungal biomass effectively reduces lead, cadmium, copper quickly. Results statistically significant, demonstrating reliability. Sustainable, cost-effective alternative to chemical treatments. Keywords: Heavy Elements, Aspergillus Terries, Rhizopus Oligosporium, Fungal Biosorption, Non-Living Biomass